Peningkatkan Upaya Sikap Moral Masyarakat Dalam Pencegahan Korupsi Untuk Memperbaiki Kualitas Kesejahteraan Masyarakat - Richardo, Albert; Marcelino, Julius; Jonathan (Nusantara: Jurnal Pendidikan, Seni, Sains dan Sosial Humaniora, 2022)
Welfare is a condition where people get the necessities of life and their rights. Therefore welfare in society is very important, currently the quality of social welfare is declining because the moral attitude in society has also decreased. Moral attitude is an individual attitude that can distinguish between right and wrong. The decline in moral attitudes can lead to bad actions, such as corruption. Corruption is an act that violates rules or norms by taking and misusing state or company money for personal or group interests with the aim of gaining personal or group benefit. The KPK noted in 2020, that corruption cases in Indonesia reached 66 investigations, 60 investigations, 71 prosecutions, 59 inkracht cases and executed 51 cases. The impact of corruption is that it can worsen the quality of society and the state in all aspects. Therefore it is necessary to improve the moral attitude of society to prevent corruption so that people's welfare improves. The research will focus on explaining corruption, previous corruption cases and prevention in the form of anti-corruption. The research aims to explain the dangers of corruption and improve people's moral attitudes to improve people's welfare. The research method in this research is qualitative with literature study data collection techniques through observation, observations in scientific journals, articles and websites related to corruption. It can be concluded that morals are very important in one's life, things that disturb society are bad behavior caused by a decrease in moral attitudes, an example is corruption. Corruption is very dangerous for the younger generation, politics, economy and bureaucracy. Therefore, to improve the moral quality of society, anti-corruption can be implemented in the life of the community itself. There is also the Ministry of Education and Culture's Anti-Corruption Education program which aims to prevent corruption.